FACTORS INFLUENCING COMPETITIVENESS OF MSMES IN EAST JAVA - R. Agus Baktiono; Sri Handini (Universitas Dr. Soetomo, 2023)
In East Java, there are numerous centers of Micro Small and Medium Enterprises (MSMEs) with each having its unique characteristics on the products. To determine the competitiveness level of MSMEs, there are numerous different perspectives possible to be used including the orientation of social capital, intellectual capital, entrepreneurship, technology, innovation, market, and competitiveness.In running the business, the MSME business sector has to be oriented towards the seven aspects in order that the business to be successful and able to survive in the present era of global competition. The independence of MSME business sector reflects the competitiveness level of the existing products available in the market.Competitiveness is the ability of a national economy to achieve a highly sustainable economic growth. It includes proper policies, suitable institutions, and other supporting economic characteristics that make a highly sustainable economic growth possible to achieve. The results of the study later found that out of 17 variables used as the forming factors namely Factor 1 (Component 1), Factor 2 (Component 2),Factor 3 (Component 3), and Factor 4 (Component 4) each had a high correlation coefficient of consecutively 0.768, 0.960, 0.786, and 0.901; meaning that each of the correlation levels was high as the value was > 0.5.Thus, Factor 1, Factor 2, Factor 3, and Factor 4 were said to be appropriate to be used representing the 17 independent variables which affected the competitiveness level of the MSMEs business sector in five cities in East Java, Indonesia. Keywords: factor analysis; competitiveness